Kebijakan Hukum Pidana Terhadap Pertanggung Jawaban Pidana Penguasaan Tanah Tanpa Hak Sebagai Tindak Pidana Ringan (Studi Pengadilan Negeri Lubuk Pakam) - Br. Sitepu, Selly Regina; Ediwarman, Ediwarman; Marlina, Marlina; Amal, M. Ridha Haikal (Universitas Medan Area, 2020)
Criminal legal arrangements regarding liability for land tenure without rights are found in the provisions of Article 6 paragraph (1) jo. Article 2 of Law No. 51 / PRP / 1960 concerning Prohibition of Use of Land without a Right of Permit or Proxy, Article 167 of the Criminal Code, Article 385 paragraph (1) of the Criminal Code. Factors causing land ownership without rights are: Lack of community legal awareness and lack of community legal knowledge. The criminal law policy on criminal liability for control of land without rights as a minor crime is in the form of a penalty in which the perpetrators of the criminal act of controlling land without rights can be submitted to court on the basis of committing criminal acts in the form of violations and in the form of non-penal actions in the form of mediation between the mastering actors land without rights with the right owner.